Pengaruh Modal Intelektual pada Kinerja Lembaga Perkreditan Desa di Bali - Pande, I Wayan Bagus; Darmawan, I Putu Aditya Surya; Yuliastuti, Ida Ayu Nyoman; Manuari, Ida Ayu Ratih; Tandio, Daniel Raditya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Village credit institutions (LPD) have very tight competition in getting customers. LPD has main competitors in the financial business, namely public banks, people's credit banks, cooperatives, Bumdesa which operates in the savings and loans sector, moneylenders and financial technology (fintech). This research aims to analyze the influence of non-financial resources, namely intellectual capital, on LPD performance in Bali. The research population was 1433 LPD with a sample of 100 LPD. The sampling method uses a stratified proportional random sampling technique. The data analysis technique uses multiple regression analysis. The research results show that structural capital, social capital and reputation capital have a positive effect on LPD performance in Bali.